Quaternionic symmetry of linear dynamical systems - Pereira, Ricardo (2007)
In this paper we study a particular kind of symmetry of linear dynamical systems, the quaternionic symmetry. After giving some basic notions about quaternions and behavioral systems, we introduce and characterize linear systems with quaternionic symmetry. Finally we propose a state-space realization algorithm for input/output systems.